The Relationship of Gross Motor Ability to Early Childhood Cognitive Ability - Risa Herdiyana Bastian; Syifa Nurbait (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2022)
This study aims to find out and explain the picture of gross motor skills in early childhood, cognitive abilities of early childhood and the relationship of gross motor abilities with cognitive abilities in early childhood.  The research method used in this study is the correlational method.  The sample in this study was 16 grade B students of Tunas Cempaka Kindergarten who had an age of 5-6 years. The data collection instruments in this study used TGMD-2 for gross motor ability and observation sheets for cognitive abilities. The conclusion of the data analysis results is that gross motor ability is in the average category, cognitive ability is in the category of developing according to expectations (BSH) and positively there is a relationship between gross motor ability and cognitive ability in early childhood.